2022
DOI: 10.3389/fsurg.2022.1019425
|View full text |Cite
|
Sign up to set email alerts
|

Case report: Balloon compression for cervical chyle leakage post neck dissection

Abstract: Postoperative chyle leakage (CL) is a rare but severe complication after neck dissection, and most patients with this complication can be treated conservatively. However, in patients with high-flow leakage, efficient and well-tolerated conservative treatment options are still lacking, and the treatments can be complicated. In this study, we report a case with CL of 1100 ml/day after neck dissection that was successfully treated by balloon compression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Fifty-one reports were retrieved and assessed for eligibility. Finally, 40 articles were shortlisted and included in this review 7 - 46 . ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Fifty-one reports were retrieved and assessed for eligibility. Finally, 40 articles were shortlisted and included in this review 7 - 46 . ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In the 40 studies, 139 patients were reported to have CL after head and neck surgeries (26 left neck dissections, 4 right neck dissections, 19 bilateral neck dissections, 85 neck dissections with side unspecified, and 6 patients who underwent other procedures of the neck such as lobectomy, thyroidectomy, or parathyroidectomy) 7 - 46 . ( Table 1 , Supplementary Table 1 )…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation